2020
DOI: 10.1016/j.wneu.2020.05.087
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgery Residents' Perspective on COVID-19: Knowledge, Readiness, and Impact of this Pandemic

Abstract: BACKGROUND: The novel coronavirus disease (COVID-19) is a life-threatening illness, which represents a challenge to all health care workers. Neurosurgeons worldwide are affected in different ways.-OBJECTIVE: This is the first study regarding the readiness of neurosurgery residents for the COVID-19 pandemic and its impact. The aim is to identify the level of knowledge and readiness and the impact of this virus among neurosurgery residents in different programs.-METHODS: A cross-sectional analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
2
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 12 publications
(32 reference statements)
3
82
2
6
Order By: Relevance
“… 33 , 34 The constant fear of bringing home the virus to one’s family only adds to the trainees’ physical exhaustion and psychological stress during this time. 7 , 35 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 33 , 34 The constant fear of bringing home the virus to one’s family only adds to the trainees’ physical exhaustion and psychological stress during this time. 7 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…drafted the survey questionnaire based on previously published studies on COVID-19 and neurosurgical practice. 7 , 15 , 16 , 18 , 19 The co-authors, who are consultant neurosurgeons involved in neurosurgical training in their respective countries, vetted the questions and revised items as necessary. The final survey instrument consisted of 33 questions ( Appendix A ) and took 5 minutes to complete.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early attention was appropriately placed on clinical adaptations to ensure that patients and providers had all the safeguards possible in place during COVID-19 to preserve life and “flatten the curve.” Similarly, many changes have been made to clinical neurosurgery practice and resident research and training. 1 , 2 , 3 However, efforts to minimize the significant effects on subspecialty medical student (MS) education (MSE) have received less attention but could, arguably, have longer term effects, especially on subspecialty fields. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…Most programs have reduced resident COVID exposure risk by reducing the number of residents in the hospital at once and reducing the number of days per week that each resident works. 3 Al-Haj et al 4 reported an 80% change in studying hours during COVID-19 among neurosurgical residents. Nonetheless, the number of study hours might be affected positively or negatively.…”
mentioning
confidence: 99%